2016
DOI: 10.1245/s10434-016-5132-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CTNNB1 Mutation Status with Progression Arrest Rate in RECIST Progressive Desmoid-Type Fibromatosis Treated with Imatinib: Translational Research Results from a Phase 2 Study of the German Interdisciplinary Sarcoma Group (GISG-01)

Abstract: Mutations at position S45 were overrepresented in the GISG-01 trial recruiting RECIST progressive patients only. The positive correlation of CTNNB1 mutation status with the progression arrest rate after imatinib therapy supports the idea of a potential predictive impact of the mutation status on DF treatment decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 22 publications
0
31
1
1
Order By: Relevance
“…Knowing the mutational status of patients at diagnosis could enable clinicians to decide between a low dose of sorafenib alone (T41A and wild‐type DTs) versus a low dose of sorafenib in combination with an autophagy inhibitor (S45F DTs), which could obviate some of the undesirable adverse effects observed in the higher doses of sorafenib. In contrast to our results, Kasper et al observed a positive correlation between S45F‐mutated patients and imatinib progression arrest rate. However, this study had an overrepresentation of S45F mutations and a remarkably lower percentage of wild‐type DTs.…”
Section: Discussioncontrasting
confidence: 99%
“…Knowing the mutational status of patients at diagnosis could enable clinicians to decide between a low dose of sorafenib alone (T41A and wild‐type DTs) versus a low dose of sorafenib in combination with an autophagy inhibitor (S45F DTs), which could obviate some of the undesirable adverse effects observed in the higher doses of sorafenib. In contrast to our results, Kasper et al observed a positive correlation between S45F‐mutated patients and imatinib progression arrest rate. However, this study had an overrepresentation of S45F mutations and a remarkably lower percentage of wild‐type DTs.…”
Section: Discussioncontrasting
confidence: 99%
“…Immunohistochemically, the fibroblasts show nuclear and cytoplasmic positivity for β-catenin. CTNNB1 mutations have been detected in up to 85.0% of sporadic DTF cases [8], resulting in the stabilization and translocation of β-catenin into the nucleus where it acts as a transcription factor. It was also demonstrated that the 5-year recurrence-free survival rate of DTF patients with these mutations is significantly worse than that of patients with wild-type CTNNB1 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no reliable tool for choosing the best systemic treatment in progressive desmoid tumor. However, some studies suggest that desmoid tumors harboring CTTNB1 mutations are more sensitive to imatinib than desmoid tumors without CTTNB1 mutations [44], and the CTTNB1 S45F mutation is associated with resistance to NSAIDs (meloxicam) compared to other mutations or the absence of mutations (4/4 vs. 9/29) [48]. Further clinical trials are urgently needed to identify predictive factors and properly assess the activity of the treatment using randomized trials and trials using quality of life data.…”
Section: Management Of Desmoid Tumormentioning
confidence: 99%